KATEGORI DAN EKSPRESI LINGUISTIK DALAM BAHASA SASAK PADA RANAH PERTANIAN TRADISIONAL: KAJIAN ETNOSEMANTIK - Saharudin Syarifuddin (Adabiyyāt: Jurnal Bahasa dan Sastra, 2012)
The study aims at describing linguistic categories and expressions of traditional Sasak farmers in Lombok Island based on their social and cultural context. Qualitative method is employed in this research. The data are analyzed using componential analysis. The analysis tries to describe the lexicons and linguistic expressions on agricultural domain. The findings show that the agricultural sphere always raises the terms of the linguistic expressions/categories. Linguistic expressions form the verb and noun categories. The order of classification or the categorization of the linguistic expressions–both for the nouns and verbs– was based on the sequence of farming activities and the results obtained. Therefore, the existing categorization is based on the generic meaning components adjusted to the process and outcome—verbs and nouns—in the domain.